The development of persistent criminality (Oxford : Oxford University Press, 2009)
This volume bridges the gap between the criminological literature, which has recently focused on the existence of various criminal trajectories, and the developmental psychology literature, which has focused on risk factors for conduct problems and delinquency.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Recidivists; Criminology; Criminals; Crime